Isolated Pulmonary Infective Endocarditis with Septic Pulmonary Embolism Complicating a Right Ventricular Outflow Tract Obstruction: Scarce and Devious Presentation. (9th September 2013) - Abdelbar, Abdelrahmen; Azzam, Raed; Yap, Kok Hooi; Abousteit, Ahmed
Abstract : We present a case of a fifty-three-year-old male who presented with severe sepsis. He had been treated as a pneumonia patient for five months before the admission. Investigations revealed isolated pulmonary valve endocarditis and septic pulmonary embolism in addition to undiagnosed right ventricular outflow tract (RVOT) obstruction. The patient underwent surgery for the relief of RVOT obstruction by substantial muscle resection of the RVOT, pulmonary artery embolectomy, pulmonary valve replacement, and reconstruction of RVOT and main pulmonary artery with two separate bovine pericardial patches. He was discharged from our hospital after 6 weeks of intravenous antibiotics. He recovered well on follow-up 16 weeks after discharge. A high-suspicion index is needed to diagnose right-side heart endocarditis. Blood cultures and transesophageal echocardiogram are the key diagnostic tools.